Perkawinan Sejenis Menurut Hak Asasi Manusia Dalam Perspektif Hukum Islam - Sanawiah Sanawiah (Anterior Jurnal, 2016)
Purpose of this study is to analyze that the homosexual marriage in accordance with human rights which is just and civilized, and to determine the homosexual marriage according to the marriage act and the perspective of Islamic law. The method used is a method normative considering that this study emphasizes that the secondary data that is studying and reviewing principles, materials and positive legal principles that of the materials libraries that exist in legislation marriage law and human rights law in Indonesia. Results from this study showed that the homosexual marriage in the name of human rights it violates human rights itself. Because the rights that should be fought is right according to the nature of natural and ordained by God, since man was created in pairs regarding marriages recognized by the state is only marriages between men and women can also be seen in Article 34 paragraph (1) of the Act Number 23 the Year 2006 concerning population administration.